Biohydrogen production from fruit and vegetable waste, sugar beet pulp and corn silage via dark fermentation. (June 2020) - Cieciura-Włoch, Weronika; Borowski, Sebastian; Otlewska, Anna
Abstract: Dark fermentative hydrogen production was investigated using sugar beet pulp (SBP), fruit and vegetable waste (FWV) and corn silage (CS). The highest hydrogen yield of 52 cm 3 /gVS was achieved for FVW treated at an organic loading rate (OLR) of 17 gVS/m 3 d. The hydrogen production from hydrolyzed SBP varied from 17 to 37 cm 3 /gVS, however the dark fermentation (DF) process was unstable due to the large amounts of lactic acid secreted by lactic acid bacteria. Moreover, in the final stage of the digester operation with SBP, a noticeable methane production of 5 cm 3 /gVS was observed. The production of hydrogen from corn silage was relatively low (24–27 cm 3 /gVS) due to operating problems and small sugar content of 7.69 g/l in this substrate. Microbiological analyses revealed the prevalence of lactic acid producing bacteria dominated by Lactobacillaceae, Coriobacteriaceae and Bifidobacteriaceae at a family level, which constituted as much as 40–60% of all detected microbes. The main hydrogen-producing bacteria were affiliated with the families Mogibacteriaceae and Ruminococcaceae . However, the most important finding was the activity of methanogens, which could grow at pH below 6 and produce methane thus lowering hydrogen yield, which was particularly visible in SBP experiments. Highlights: FVW was characterized by the highest hydrogen yield of 52 cm 3 /gVS. Hydrolyzed SBP produced both hydrogen and methane, despite low pH. Corn silage was difficult to treat due to clogging problems. Lactobacilllaceae, Coriobacteriaceae and Mogibacteriaceae were dominant bacteria families. Lactic acid bacteria and methanogens hampered hydrogen production.